Synthesis of carbide lime derived strong base catalyst for biodiesel production - Lim H.H.; Pua F.L.; Rohaya O.; Taufiq-Yap Y.H.; Sharifah N. (Trans Tech Publications Ltd, 2023)
Biodiesel; Calcium carbonate; Calcium fluoride; Carbon dioxide; Esters; Fatty acids; Fourier transform infrared spectroscopy; Hydrated lime; Lime; Morphology; Palm oil; Potassium compounds; Scanning electron microscopy; Sunflower oil; Temperature programmed desorption; Transesterification; Base catalyst; Base strength; Biodiesel production; Carbide lime; Catalyst loadings; Structure and morphology; Temperature-programmed desorptions; Test temperatures; Transesterifications; ]+ catalyst; Catalysts